Response Surface Methodology as an Experimental Strategy for Ultrasound-Assisted Extraction of Phenolic Compounds from Artichoke Heads - Valentina Melini; Francesca Melini; Francisco Javier Comendador (MDPI AG, 2023)
The accurate quantification of phenolic compounds (PCs) in foods has become mandatory for a reliable estimation of PCs dietary intake. However, the extraction step of these molecules from the food matrix is a challenging and complex task. To manage the current lack of an official or generally accepted procedure for the recovery of phenolics, the application of statistical and mathematical tools, such as the response surface methodology (RSM), that allow the optimization of extraction parameters and the acquisition of the best output, has become the analytical approach of choice. The aim of this study was to apply an RSM-optimized ultrasound-assisted procedure to extract phenolic compounds from artichoke (Cynara cardunculus L. var. scolymus (L.) Hegi, cultivar "Campagnano") heads. The effect of extraction time, temperature, and solvent-to-sample ratio on the profile and content of phenolic acids and flavonoids was investigated. The total phenolic content was 488.13 ± 0.56 mg GAE 100 g−1 dry matter (dm) and total flavonoid content was 375.03 ± 1.49 mg CATeq 100 g−1 dm when the optimum extraction conditions were set. The HPLC analysis showed that caffeoylquinic acid derivatives (i.e., cynarin and 1,5-O-dicaffeoylquinic acid) were the main compounds in globe artichokes. Caffeic and p-coumaric acids were also identified. In regard to flavonoids, only the flavone luteolin-7-O-glucoside was identified.